PRE-SERVICE ENGLISH TEACHERS’ PERCEIVED READINESS FOR TECHNOLOGY-ENHANCED LANGUAGE LEARNING (IAIN Syekh Nurjati Cirebon, 2022)
In 21st century, the use of the Internet and digital technology in second and foreign language learning and acquisition is predominant. Therefore, concern for language teachers’ competence in utilizing technology in their classrooms is growing. This study aims to investigate pre-service English teachers’ perceived readiness for TELL in Indonesian context. A case study design with survey and semi structured interviews was employed. The participants were 21 pre-service EFL teachers taking a course on Artificial Intelligence for language learning and teaching. The pre-service English teachers’ readiness is examined from four components: (1) basic digital skills, (2) didactic ICT competence, (3) learning strategies, and (4) digital bildung. The result suggests that a significant portion of the pre-service teachers involved in this study perceived themselves as competent and ready to implement TELL in their EFL classroom after completing their teacher training program.